Chinese college students’ management of their online identities - Qin, Yue (2018)
The Internet has provided a new context for the exploration of the concept of identity. This study used innovative perspectives in studying the online identities of a group of college students in China. (1) The study explored the individual ‘you’ rather than a collective identity. (2) The study linked all meaningful online settings which are suggested by the participants in discussions of the concept of online identity. (3) The study adopted the dialogical conception of identities of DST (Dialogical Self Theory) that gave each ‘I-position’ an opportunity to express its own story from its own perspective. Thus, the present study explored all the ‘I-online-positions’ and ‘dialogical relationships’ among them. (4) Comparing the relationships between the online and offline identities aimed to locate the concept of online identity and a comprehensive understanding of the whole concept of identity. Furthermore, it explored not only the relationship between the whole concept of online and offline identity, but also the relationship between each online sub-identity and the offline identity, with the aim to locate a more precise position for the online identity. Methodologically, the study settled in the transition zone between interpretivism and pragmatism, valuing philosophical stances from both of them. It also adopted a situationalist position by valuing the complementarity of quantitative and qualitative approaches. Data collection involved two stages: a questionnaire followed by in-depth interviews. These process were conducted under the concept of a ‘participatory sense-making’ relationship between the researcher and the researched. The study arrived at the following conclusions: (1) ‘Situational self’: there are different online identites in different online environments, each satisfying different needs of the individual and influenced by personal and cultural values, the specific environment and personal imagination. (2) ‘What is lacking tends to appear online’: each participant wants to achieve his/her own ‘circle’ of his/her offline identity online. (3) ‘Changeability’ of online identity: contrary to the relative stability of offline identity, a ‘changeability’ of online identity satisfies online users’ needs. Online identities are dropped or tend to converge with offline identities if certain needs are met. (4) ‘Beneficial to the college students’: most participants claim the transitions between various identities quite smooth and the experiences with online identities are quite beneficial to most. The exception to this is a case of addiction. (5) The personal ‘circle of imagination’ is the starting point of an individual’s engagement with identity choices, in the interaction between personal and cultural values. (6) ‘Rational man’: the participants reveal themselves as ‘rational’ in choosing the most advantageous online identities to meet their own needs, based on their personal values, cultural values, specific environments and personal imagination.